2006
DOI: 10.1063/1.2219003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of barrier process on electromigration reliability of Cu/porous low-k interconnects

Abstract: Electromigration ͑EM͒ reliability of Cu/low-k interconnects with a conventional preclean-first process, and an advanced barrier-first process has been investigated. Compared with the preclean-first process, extrinsic early failures were not observed for the barrier-first process. This suggests that process-induced defects, which are the most probable cause for early failures, are significantly reduced for the barrier-first process. Transmission electron microscopy observation demonstrated a more uniform and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…For both electron flow directions, capping an SiCNH layer increased the lifetimes of the Cu interconnects embedded in dense SiCOH films; those embedded in porous SiCOH films behaved similarly. Surface migration has been reported as a dominant EM failure mechanism for Cu interconnects, 30,31 and could be also responsible for the finding of this study. Capping an SiCNH layer on the top surface of a Cu wire is equivalent to transferring the weak interface of Cu/SiCOH to a strong one of Cu/ SiCNH, thus slowing down the surface migration due to an enhancement of adhesion for the interface of Cu/SiCNH.…”
Section: Resultssupporting
confidence: 58%
“…For both electron flow directions, capping an SiCNH layer increased the lifetimes of the Cu interconnects embedded in dense SiCOH films; those embedded in porous SiCOH films behaved similarly. Surface migration has been reported as a dominant EM failure mechanism for Cu interconnects, 30,31 and could be also responsible for the finding of this study. Capping an SiCNH layer on the top surface of a Cu wire is equivalent to transferring the weak interface of Cu/SiCOH to a strong one of Cu/ SiCNH, thus slowing down the surface migration due to an enhancement of adhesion for the interface of Cu/SiCNH.…”
Section: Resultssupporting
confidence: 58%
“…It is well known that the poor interfacial adhesion energy at the Cu=capping layer interface could be the key reason for the EM reliability degradation. [12][13][14] There have been several reports on the effects of Cu surface treatments and oxidation environments on the interfacial adhesion at the Cu and capping layer interface. [8][9][10][11][12][13][14][15] Previous studies on the interfacial adhesion between Cu and a SiN x capping layer after CMP, focusing on surface treatments with various plasma gases and wet chemical solutions, showed that the surface treatments can remove contaminants and residual oxygen at the Cu surface after CMP and thereby improve the interfacial adhesion energy.…”
Section: Introductionmentioning
confidence: 99%
“…This increase is becoming larger with the advance of technological node because the metal barrier would occupy a larger fraction of the metal line. 13 Traditionally, Ta/TaN bilayer is widely used as a metal barrier. In additional to an increased line-resistance, this barrier exhibits reduced barrier capacity and poor step-coverage, in the scaled trench as technological nodes advances to 32 nm or below.…”
mentioning
confidence: 99%